Comparative Evaluation of a Novel Recombinase Polymerase Amplification-Lateral Flow Dipstick (RPA-LFD) Assay, LAMP, Conventional PCR, and Leaf-Disc Baiting Methods for Detection of Phytophthora sojae - Dai, Tingting; Yang, Xiao; Hu, Tao; Jiao, Binbin; Xu, Yue; Zheng, Xiaobo; Shen, Danyu (Frontiers in Microbiology, 2019)
Early and accurate detection of the causal pathogen Phytophthora sojae is crucial for effective prevention and control of root and stem rot and seedling damping-off of soybean. In the present study, a novel isothermal amplification assay was developed for detecting P. sojae. This 25 min assay included a two-step approach. First, a pair of novel primers, PSYPT-F and PSYPT-R were used to amplify a specific fragment of the Ypt1 gene of P. sojae in a 20 min recombinase polymerase amplification (RPA) step. Second, lateral flow dipsticks (LFD) were used to detect and visualize RPA amplicons of P. sojae within 5 min. This RPA-LFD assay was specific to P. sojae. It yielded negative detection results against 24 other Phytophthora, one Globisporangium, and 14 fungal species. It was also found to be sensitive, detecting as low as 10 pg of P. sojae genomic DNA in a 50-μL reaction. Furthermore, P. sojae was detected from artificially inoculated hypocotyls of soybean seedlings using this novel assay. In a comparative evaluation using 130 soybean rhizosphere samples, this novel assay consistently detected P. sojae in 55.4% of samples, higher than other three methods, including loop-mediated isothermal amplification (54.6%), conventional PCR (46.9%), and leaf-disc baiting (38.5–40.0%). Results in this study indicated that this rapid, specific, and sensitive RPA-LFD assay has potentially significant applications to diagnosing Phytophthora root and stem rot and damp-off of soybean, especially under time- and resource-limited conditions.